C-Reactive Protein (CRP) Levels in Babies with Gastroschisis Managed with Preformed Silos - Ram, Ashok Daya; Drewett, Melanie; Burge, David (European Journal of Pediatric Surgery, 2013)
Background/Purpose The purpose of this study was to assess the degree of elevation of serum C-reactive protein (CRP) levels in infants with gastroschisis managed by placement of a preformed silo and subsequent nonoperative closure.Methods CRP measurements were collected prospectively in infants with gastroschisis undergoing preformed silo placement until defect closure. Infants requiring operative closure or surgical silo placement were excluded as were any infants with confirmed sepsis during the closure period.Results Data were available for 43 infants. Median CRP at birth was 8 mg/L (range 6 to 55) rising to 42 mg/L (range 35 to 68) at the time of closure.Conclusions Elevation of serum CRP levels is to be expected in infants with gastroschisis managed with a preformed silo in the absence of infection. This data may be used to prevent unnecessary use of antibiotics in this group of patients.
Keywords: gastroschisis; C-reactive protein (CRP); silo